An alternative method of doing extra-oral maxillary nerve block - Hui, John-Edike W.
8 volunteers, 4 males and 4 females ranging in age from 18 to 32 years old, were used in this study to verify the effectiveness, degree of traumatism induced and level of acceptability by the subjects in the precoronoid route of extra-oral maxillary nerve block. The result turned out to be: "The extra-oral maxillary nerve block is effective, atraumatic but however not preferred by the subjects."